Factores de éxito en las unidades de negocio de caña flecha en el municipio de Sampués, Sucre, Colombia (2021)
The objective of this article was to determine the factors that influence the success of the arrow cane handicraft business units in the municipality of Sampués-Sucre, Colombia, according to the Resources and Capabilities Theory (TRC). The research was carried out under a descriptive quantitative approach, the sample consisted of 320 informal and formal artisan workshops engaged in this craft. During the research process, Pearson’s bivariate correlation and multiple linear regression analyses were carried out to identify the factors that influence the success of these businesses. Among the findings, production technologies, schooling, financial control, organizational innovation, information technologies, quality improvements,business management skills, process management and the ability to differentiate the product are the factors associated with the success of these handicraft workshops.